An Exploration of Tennis Consumption Experiences by a Beginner Named 'Te-rin-e': The Desire for Self-Expression, Conflict with Mainstream Culture, and Knowledge-Based Consumption - Seami Lim; Howon Jeong; Hanbeom Kim (Cheyuk gwahag yeon-gu, 2023)
PURPOSE This study focuses on the experiences of novice tennis enthusiasts in Korea, aligning with the rising popularity of tennis as a burgeoning cultural phenomenon. METHODS Employing an ethnographic approach, we included eight participants with <5 years of tennis, in addition to three auxiliary participants. RESULTS The primary findings of this study are as follows: First, novice tennis players from the MZ generation actively employ tennis as a means of personal expression, sharing their tennis-related fashion and experiences on SNS. Second, most novice tennis players report a sense of detachment from the traditional club-centric tennis culture, gravitating toward casual court usage, spontaneous activities, and flexible membership structures. F inally, despite their modest technical proficiency, they avidly engage in knowledge-based consumption, displaying a profound grasp of tennis-related information. CONCLUSIONS These findings provide valuable insights into comprehending this burgeoning cultural phenomenon in Korean society, stemming from the escalating interest in tennis, and can serve as a valuable benchmark for establishing development strategies for tennis.